Open innovation model within public research and innovation programmes - Bonecki, Mateusz (Filozofia Publiczna i Edukacja Demokratyczna, 2016)
The paper concerns the role of open innovation within public R&D&I programmes. The history of innovation management shows that the methods used to organize research and development work have evolved towards open innovation model. The first, original, concept of “open innovation” (Chesbrough) has been coined to explain how companies diversify technology sourcing and commercialization methods, and thus represents a perspective of industry. On the other hand, Open Innovation 2.0 approach emerged in the context of policy-making and displays features characteristic of innovation systems theory. It enables a more indepth analysis of interactions between different types of actors involved in innovation process and complex R&D ecosystems.